Faliure menance in engineering conference (2011)
The collapse of building structures in recent time has become a source of worry for the professionals in the building industries with particular attention being on cement concrete structures. This paper however examined the causes and remedy to the ever increasing failure of mud buildings in cores of our major cities in Nigeria with particular focus on Ibadan South East Local Government Area of Ibadan, Oyo state. The major causes and nature of the failures of mud buildings, evaluation of the strength of failed buildings and the ones in service, and environmental impact of the collapsed buildings on the inhabitants were examined. Data used for this study were collected by the use of structured questionnaires, oral interviews, field trips made to selected areas to ascertain common failure of buildings and the use of Schmidt hammer to test the compressive strength of some selected mud buildings in the study areas. Secondary data were also obtained from local government officials and few published journals. It was observed that failure occur due to lack of adequate maintenance, improper alteration, poor planning of the area, vibrations from vehicles, poor drainage system, and poor solid waste management due to bad road network, material incompatibilities and primitive method of construction. Appropriate preventive measures were provided in the study as means of preventing future occurrence of the failures.